Updates on the diet items of Conophis lineatus (Squamata: Dipsadidae) - Carlos Javier Pérez-Alvarado; Víctor Vásquez-Cruz (Caldasia)
Conophis lineatus is a widely distributed species, from Mexico to Costa Rica, recognized for its wide diet breadth. Here we present two feeding events under natural conditions, as well as a review of liter-ature on the species in the diet of C. lineatus.